Measuring the Software Quality of Government Website by Applying McCall Methods - Megah Bensuniara; Rahma Fitria (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
This study measures the quality of the eKinerja Application of the Communication and Informatics Service of Bener Meriah Regency after conducting a literature study, this study began by distributing questionnaires compiled based on the McCall method. The McCall method is one of the methods that can be used to measure software quality, then the results of filling out the questionnaire are tested for validity and reliability to obtain valid and reliable variables and indicators. In the test, there were 177 people who became respondents in this study. These variables and indicators are then used to measure the quality value (Fa) of each variable, the measurement begins with the process of weighting variables and indicators through questionnaires filled out by experts. The weighting uses a scale of 0.1 to 0.5 for each variable Correctness, Reliability, Efficiency, Integrity and Usability along with their respective indicators. The results of the McCall method calculation on the quality of the Bener Meriah Regency Communication and Informatics Service Performance Application show that the correctness quality factor gets a good category with a percentage result of 74% from the usability factor getting a result of 60% with a fairly good category, the integrity factor getting a result of 77% with a good category, from the reliability factor getting a result of 83% with a very good category from the efficiency factor getting a result of 46% with a bad category.